2021
DOI: 10.1186/s40729-021-00301-6
|View full text |Cite
|
Sign up to set email alerts
|

Laser microgrooved vs. machined healing abutment disconnection/reconnection: a comparative clinical, radiographical and biochemical study with split-mouth design

Abstract: Background Repeated removal and replacement of healing abutments result in frequent injuries to the soft tissues. Purpose The purpose of this study was to evaluate the effect of disconnection/reconnection of laser microgrooved vs. machined healing and prosthetic abutments on clinical periodontal parameters, marginal bone levels, and proinflammatory cytokine levels around dental implants. Material and methods … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 37 publications
0
15
0
Order By: Relevance
“…In radiographic imaging, the problem of artefacts is always present, but peri-implant bone defect evaluation, or studies about bone morphology near the implant, are still being carried out [51].…”
Section: Implantologymentioning
confidence: 99%
“…In radiographic imaging, the problem of artefacts is always present, but peri-implant bone defect evaluation, or studies about bone morphology near the implant, are still being carried out [51].…”
Section: Implantologymentioning
confidence: 99%
“…erefore, there is less stress in the abutment screws as compared to the external butt joint. e cold welding inherent to this system favors the torque gain as the friction between the internal implant surfaces and the conical abutment, which makes high stability [6][7][8].…”
Section: Introductionmentioning
confidence: 99%
“…This conclusion, however, finds a further explanation in the rather short follow-up studies on more numerous samples and with 10-year follow-up studies, all of which have revealed high levels of inflammation. Specifically, this assessment must be noted for the results of the study by Kiran et al, which are also justifiable for short follow-ups [ 33 , 34 , 35 ].…”
Section: Discussionmentioning
confidence: 99%